PROLONGED GESTATION IN A BUFFALO WITH HYDROAMNIOS ASSOCIATED WITH FETAL MONSTER: A CASE REPORT - HONPARKHE, M; GHUMAN, S P S; KUMAR, AJEET (The Indian Journal of Animal Reproduction, 2010)
A buffalo having prolonged gestation with hydroamnios associated wlth feta! head malformationswas delivered per-vaginum after partial fetotomy.
Keywords: Buffalo; Hydroamnion; Fetotorny